Road Geometric Planning at the Kertajati Toll Gate Towards Kertajati International Airport - Zahran Ditra Fadillah; Andri Irfan Rifai; Adinda Fajarika (LEADER: Civil Engineering and Architecture Journal, 2024)
Roads are a very important infrastructure facility to connect one area to another. Indonesia with a large population result in the need for adequate infrastructure such as in terms of transportation. One of them is the West Java International Airport, to get to this place you need adequate access. So, you need precise, ideal, and fast road geometric planning using AutoCAD Civil 3D. This research using AutoCAD Civil 3D software aims to improve efficiency and optimize the Jatibarang-Kadipaten road. The method used in this study uses qualitative methods. The results of this study are to have 2 bends in the horizontal alignment with the Spiral-Cyrcle-Spiral bend type and the excavation and embankment volumes are 1562203.72 m2 and 36412.31 m2.